Against Any Theory: Rapid Consolidation of Democracy in Central and Eastern Europe - Wolggang Merkel (Anali Hrvatskog Politološkog Društva, 2006)
The author polemises with once infl uential theories of transformation – whose greats are Jon Elster and Claus Off e – which were based on the theorem that a simultaneous successful economic and political – and, somewhere, state – transformation in Eastern Europe is not possible. Contrary to these theories, in most post-communist countries of Eastern Europe democracy has consolidated rather quickly. The author demonstrates this proposition by measuring the consolidation of new democracies according to Bertelsmann’s transformation index (BTI) at four levels: the constitutional and representative level, and the levels of behaviour of actors and political culture. Failures in the analysis of transformation processes are blamed on the theories of action that simply transplanted the ‘transitional paradigm’ from Southern Europe and Latin America into Eastern Europe. Theories of actors seek to deduce highly complex changes of systems in this region from highly formalised and oversimplifi ed constellations of actors, ignoring the very diff erent democratisation potentials of individual countries. Thus, three variables are left in ‘theoretical obscurity’ – modernity, statehood and external actors – which are placed in the focus of modernisation theories, system theories and structuralist theories, and which prove to be extremely important for the understanding of transformation processes in Eastern Europe.